Apontamentos da produção do riso na adaptação de Romeu e Julieta pela Turma da Mônica - Luiz, Tiago Marques (2019)
Talk about adaptation is not just a change from one semiotic code to another, because the phenomenon is really complex and trying to summarize its process to a simple transfer is to incur in a problematic statement. Adaptation, for this PhD dissertation, as a phenomenon of Intermidiality, is not only a process of transition, but a set of stages that will result in the adapted text, taking into account the particularities of this first textual genre in relation to the second media or other media that will shape it, as well as the linguistic, social and cultural aspects of the source text and the adapted text. The proposal of this research is to make a microstructural comparison regarding the parody of the Shakespeare's Romeo and Juliet text, by Mauricio de Sousa Productions, resulting in the audiovisual text Monica and Jimmy Five: in the World of Romeo and Juliet, broadcasted by TV Bandeirantes in 1979. In order for this research to take shape, it was necessary to make a theoretical contribution from the Adaptation Studies, from Intermidiality’s theoretical framework and from Humor Studies, more specifically on parody and laughter, through the reflections from Robert Stam, Thaïs Diniz, Claus Clüver, Vladmir Propp, Henri Bergson, Ivo Bender, among others. The methodology was based on the reflections by Ivo Bender and Stanislaw Baranczak, where the character, in the course of action is able to provoke laughter in the viewer/reader, through devices such as puns, irony, quiproquo, interaction between the actors in the course of the plot. Shakespeare's adaptations of Shakespeare's plays have been studied in the binomial original and copy, but this dissertation is not based on the originality’s issue, once that Shakespeare’s work, which perpetuated in these four centuries that separate him from our contemporaneity, has been re-signified in its most varied interfaces, being considered original by themselves. What instigates this dissertation is the process of parody re-creation of the Shakespearean play in the production of the Monica and Jimmy Five in the world of Romeo and Juliet television show, with an emphasis on humor and laughter. The production team of MSP - Mauricio de Sousa Produções - read the Shakespearean play, as well as read many of its many recreations over time, what was taken into account at the time of the creative process. The comparison between a verbal and a non-verbal text, as distinct means of expression that manifest a single content, in intersemiotic relation, can also be an opportunity to show the subtleties of the semiotic analysis applied to the most varied objects of signification and communication. As a prelude of the way developed in this research, it can be said that there was not only an adaptation, but a meta-creation on the part of Mauricio de Sousa Produções in relation to Shakespeare's text, combining a little of the comedy in Romeo and Juliet with comedy from Monica’s Gang. This research aims, in the first instance, to contribute to the study of Shakespearean work with a new focus; a study for Children's Literature, because, although Shakespeare is a name for theater, world literature, and also for film and television, a study linking Shakespeare and the children's audience with Monica's Gang has not yet been studied. In addition to the proposal of articulating Shakespeare with the youth public, it is expected that further researches be carried out with Mauricio de Sousa in the field of inter-media adaptation.